The Effect of Half Plunging and No Plunging as Alternative Winemaking Techniques on Phenolic Extraction and Pigment Composition of Wine - Chittenden, R.; Annand, M.; King, P.; Russell, G. (South African Journal of Enology and Viticulture, 2016)
The extraction of phenolics (anthocyanins, total phenolics and tannins) and pigmented tannin evolution in Merlot red wines made using three different winemaking techniques were evaluated over one year. Traditional maceration (TM) (two plunges per day), half plunging (half) and no plunging (NP) methods were compared using triplicate 12 kg vinification. No pre-fermentation maceration occurred and a 15-day fermentation and post-fermentation period was used. The wines were analysed daily during the 15-day maceration period and regularly after pressing during the next 11 months. Phenolic, tannin and colour measurements were analysed using UV/Vis spectral readings processed using the AWRI WineCloudTM. At the end of the 15-day maceration, total phenolics, total pigment and free anthocyanins were significantly lower in concentration in the TM treatment compared with NP. The tannin concentration also was significantly lower from days 10 to 12. Pigmented tannin was consistently at higher concentrations in the TM treatment, although not significantly so, during maceration. The significant differences were maintained as the wine developed over the next 11 months; however, the NP trial wine displayed increased pigmented tannin development compared with the TM, being significantly higher in pigmented tannin from about day 90. Higher colour and phenolic extraction in the NP trial led to higher stable colour development in the resulting wines, with the winemaking having an important effect in modifying the pigment profile of the wines. General wine quality parameters did not differ significantly between the three treatments.